First appointment of the gender Pteranthus Forsk for the European continental flora - Chueca, F. Esteve (Ars Pharmaceutica (Internet), 1968)
We have determined the amino acid content of acorn flour (Quercus Ilex) and of prickly pear (fruit of Opuntia Ficus Indica) by means of automatic analyser. We have studied various mixtures of both products with commercial fish flour with the object of discovering the best mixture from a nutritive and economic point of view. Biological and chemical tests were carried out with these mixtures, and transformation indexes were also calculated.